Integrating Pedagogical Intelligent Agent and Content Display Patterns in Virtual Learning Environments for Promoting the Skills of Digital Learning Objects Production - Yousra Amer Elwakel (International Journal of Instructional Technology and Educational Studies)
The current research aims to develop the performance and cognitive aspect of digital learning object production skills of postgraduate students specializing in educational technology using (Articulate Storyline3) program, by designing a virtual learning environment based on the interaction between multiple intelligent agent patterns (dynamic/interactive) and content display patterns (full/ partial). To achieve the research objectives, the experimental approach was followed and the research sample was divided into (94) male and female students from graduate students majoring in educational technology at the Faculty of Education, Tanta University for the academic year 2023/2024. With a quasi-experimental design consisting of (4) experimental groups, at a rate of (22) students per group, the research tools were an achievement test, an observation card for the skills of producing digital learning objects, and a final product evaluation card, taking into account the standards of designing the virtual environment and producing digital learning objects and pedagogical intelligent agent's two forms. After using the appropriate statistical methods, the research results reached the effectiveness of the proposed treatment, which is the virtual learning environment based on the interaction between the two forms of the intelligent agent and the two forms of displaying the content, in developing the skills of producing digital learning objects among graduate students majoring in educational technology. The post-measurements were in favor of the intelligent agent (interactive) group and the (partial) content display pattern. The research recommended employing the intelligent interactive agent technology in electronic learning environments for its ability to enrich the educational experience,